Recurrent cochlear implant associated seroma: A series of five patients. (4th March 2019) - Nash, Robert; Shaida, Azhar; Saeed, Shakeel; Khalil, Sherif; Lavy, Jeremy
Abstract : Introduction: We have observed a small number of patients with cochlear implants who have a tendency to develop recurrent seromas overlying the implant package. Methods: Five patients with a current or previous history of recurrent seromas presenting for review over a three-month period were identified. A retrospective review of their case notes was undertaken. Results: All patients identified were children, with a mean age at first seroma of 5.0 years (range 1.9–10.4 years). The mean interval between implantation and first episode of seroma was 3.1 years (range 0.9–6.4 years). With the exception of imaging showing a fluid-density collection, investigations were generally unremarkable. Fluid aspirated from one patient was cultured and no organisms were grown. Antibiotics, most commonly amoxicillin / clavulanic acid, were commonly but not universally prescribed. Conclusions: Recurrent cochlear implant associated seroma appears to be an idiopathic process. Investigations are generally unhelpful, and whilst it is probably prudent to treat with antibiotics during an initial presentation, once a pattern of recurrent seroma is established, patients can be treated conservatively.